THE MAKING OF ENGLISH TRANSLATION OF SIAK TOURISM OFFICE WEBSITE - Nugroho, Bintang; Elfa, Fanalisa Elfa,; Sari, Diah Paramita (INOVISH JOURNAL, 2024)
Pesona Siak is a website for promoting Siak tourism to local tourist and to international tourist but it only display in one language- Indonesian Language. The purpose of this study is to translate the content of Siak Tourism Office website – Pesona Siak into English.This study used descriptive method and the translation usedsemantic translation method.There were several processes in translating such as collecting the contents, reading and understanding, terminology, analyzing, restructuring, translating, and revision.The result of this study is English translation of Siak tourism office website and post in a wordpress website. There were several steps to create the website such as download the application, installing process, creating account, making the home page, and then posting the translation result